A cloud theory based reliability analysis method and its application to reliability problems of breakwaters. (1st August 2020) - Koç, Mehmet Levent; Imren Koç, Dilek
Abstract: This study presents a novel fuzzy random reliability analysis method based on the cloud theory and investigates its applicability employing three numerical examples related to the structural reliability of breakwaters. The results which are compared with the calculations of the traditional (i.e., MCS, FORM), as well as non-traditional (i.e., FMCS, ANN based MCS), methods show that the presented method has a good potential to easily calculate fuzzy random reliability of not only coastal but also other engineering structures. Highlights: Cloud theory (CT) easily integrates both fuzziness and randomness together. CT based reliability method successfully calculates fuzzy random reliability. CT based reliability analysis is useful in practice to assess structural reliability.